New Palaeohispanic inscriptions from the Archaeological Museum of Seville (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Three new inscriptions preserved at the Archaeological Museum of Seville are published and studied for the first time in this paper. One of them is a fake, as proved by the material on which it has been engraved and by the fact that its text is based on previously known Iberian inscriptions, especially one of the leads sheeds from Orleyl. The second inscription, which comes from La Mesa (Alcolea del Río, Seville) is a lead plaque with a short, fragmentary text. Its importance lies in the fact that it has been written a special variety of Southern Iberian writing only attested in a few inscrip- tions on lead so far. It provides new evidence of the use of diachritic marks with the signs of the Southern Iberian script and it is the second inscription showing a “circular” display of its text. The third inscription is a small  bronze fragment of unknown provenance with a few letters.
Keywords: Palaeohispanic Inscriptions; Iberian; Celtiberian; Southern Iberian Writing; Fakes; Inscriptions on Lead Plaques; Inscriptions on Bronze Plaques